Burden of Glucocorticoid Use and Risk of Toxicities Among Patients with Immunoglobulin-G4-Related Disease: A Retrospective US-Based Claims Study - Zachary S. Wallace; Jenny Y. Park; Elizabeth Serra; Patrick Gagnon-Sanschagrin; Annie Guérin; Kristina Patterson; Haridarshan Patel; Vikesh K. Singh (Rheumatology and Therapy)
Abstract Introduction Glucocorticoids are commonly used to treat immunoglobulin G4-related disease (IgG4-RD), but there is limited real-world evidence describing glucocorticoid-related toxicities in this population. This study assessed glucocorticoid use and toxicities during the first year after diagnosis among patients with IgG4-RD. Methods The IQVIA PharMetrics® Plus database was used to identify adults with IgG4-RD using a validated algorithm. Patients were stratified according to glucocorticoid use during the 12-month study period following the first observed IgG4-RD-related diagnosis (index date): low glucocorticoid use (prednisone equivalent daily dose [PEDD] < 5 mg/day) or high glucocorticoid use (PEDD ≥ 5 mg/day). Incident glucocorticoid-related toxicities were assessed during the study period and incidence was compared between groups using Chi-square tests. Results Among 295 patients with IgG4-RD, 150 (50.8%) had low glucocorticoid use, and 145 (49.2%) had high glucocorticoid use during the study period. In each glucocorticoid group, mean PEDD was highest in the 3 months post-index and subsequently decreased. At 12 months post-index, 24.7% of the low glucocorticoid use group and 60.7% of the high glucocorticoid use group were receiving glucocorticoids. The high glucocorticoid use group had a significantly higher mean (± standard deviation) number of incident glucocorticoid-related toxicities (1.8 ± 1.7 vs. 1.2 ± 1.3) and more frequently had ≥ 3 glucocorticoid-related toxicities (29.0% vs. 13.3%; both p < 0.01) compared to the low glucocorticoid use group. Specifically, cardiovascular- (29.0% vs. 18.7%), gastrointestinal- (29.7% vs. 16.0%), and infection-related (31.0% vs. 17.3%) toxicities were significantly more common in the high glucocorticoid use group than the low glucocorticoid use group (all p < 0.05). Conclusions In this retrospective, claims-based analysis, high glucocorticoid use was seen in half of patients with IgG4-RD during the first year following diagnosis. Patients with high glucocorticoid use experienced significantly more incident glucocorticoid-related toxicities than those with low use during this first year.